2008
DOI: 10.1007/s11242-008-9238-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Flow Fields in In-situ Air Sparging and its Effect on Remediation

Abstract: In-situ air sparging (IAS) is used for the clean-up of soil and groundwater that are contaminated with volatile organic compounds in relatively permeable subsurface environments. In this study, we investigated the secondary groundwater and gas flow fields that develop in the vicinity of single and multiple air sparging wells. The purpose is to evaluate their effects on contaminant plume migration and thus, remediation. Governing equations describing multiphase flow and contaminant transport in a three-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The reasons for unstable movement of air are discussed in more detail in Section 3.4.3. A part from that air sparging can lead to decrease in relative permeability of the groundwater at the injection region in case of a moving contaminant plume [139]. The system under consideration in the above cited works relating to NAPL recovery was entrapped NAPL (in form of pools and entrapped blobs) in water saturated porous medium, meaning that the interphase mass transfer occurred from both the air-water interface and the air-NAPL interface.…”
Section: Field Scalementioning
confidence: 99%
“…The reasons for unstable movement of air are discussed in more detail in Section 3.4.3. A part from that air sparging can lead to decrease in relative permeability of the groundwater at the injection region in case of a moving contaminant plume [139]. The system under consideration in the above cited works relating to NAPL recovery was entrapped NAPL (in form of pools and entrapped blobs) in water saturated porous medium, meaning that the interphase mass transfer occurred from both the air-water interface and the air-NAPL interface.…”
Section: Field Scalementioning
confidence: 99%
“…Rahbeh and Mohtar ( 2007 ) studied the positive effect of multi-phase transport models to full-scale treatment by air sparging and SVE of BTEX-contaminated site. A similar fi eld study envisaging the success of air sparging with MPE was done by Jang and Aral ( 2009 ).…”
Section: Multi 3-phase/dual-phase/vacuum-enhanced Extraction/bioslurpingmentioning
confidence: 98%
“…An in -situ air sparging system with multiple injection wells performed better than a single injection well in -situ air sparging system and was effective in capturing and remediating the detoured contaminant plume (Jang and Aral 2009 ). At fi eldscale, Kao et al ( 2008 ) showed >70 % BTEX removal within 20 months at an average groundwater temperature of 18 °C through the biosparging system.…”
Section: Air Spargingmentioning
confidence: 99%
“…One-phase sharp-interface model requires an intrinsic permeability and porosity as the only parameters and assumes a distinct free boundary between the air plume and groundwater (Nikolskii 1961). Two-three phase flow models consider combined air and groundwater (and sometimes NAPL) motion (McCray and Falta 1996;Mei et al 2002;Jang and Aral 2009) that requires phase permeabilities and capillary pressure functions, which are difficult to measure in the field. Any intermittency of AS-SVE-as in our case-involves imbibition-drainage cycles.…”
Section: Introductionmentioning
confidence: 99%